"All the same thing": liberating reproductive politics for a mediated "gay community". Issue 1 (2nd January 2019) - Booth, Karen M.
Abstract: Analyzing the logic by which the Boston-based, national newspaper, the Gay Community News (GCN), intervened in mid-1980s battles over abortion and foster-parenting, this case study confirms and complicates recent critiques of ahistorical and silo-ed "alternative" media theory. The GCN's radical collective strategically mixed, dismissed, crossed, re-defined, and ignored historically and geographically specific rhetorical resources to link abortion and lesbian/gay parenting as an "all the same thing" argument for its feminist "gay liberation" politics. At once premised on and adapting an opposition between logics of liberation and of "private" choice, the GCN's equivalence rhetoric challenges distinctions between social movement media. The case also demonstrates how, considered in their own contexts, media projects may both disrupt oppressive codes and representations, whether promulgated by the state or other activists, and reinforce or legitimize domination and privilege. Although flawed and unavoidably contingent, this creative "same thing" imagining of a feminist "gay" reproductive liberation politics, and its limits, speak powerfully still, or again, to the radical, self-interrogating, and embodied social justice solidarities urgently needed today.